Comprehensive Trade Agreements: Conditioning Globalisation or Eroding the European Model? - Annette Bongardt; Francisco S. Torres (Intereconomics, 2017)
Trade dynamics within the EU are presently pushing it towards deepening globalisation through bilateral comprehensive trade agreements which establish far-reaching rules that govern the bilateral trade relationship. The European Commission has defended these agreements as a vehicle through which to promote world trade in accordance with European values and norms. However, the theory of fiscal federalism and the principle of subsidiarity tell us that one should not centralise decisions at the supranational level which are better taken at the national or regional level when there are different preferences among countries or regions. Consequently, member state and regional competences ought not to be perceived as a mere obstacle to swift trade deals. Rather, they can provide an important checks and balances function with regard to whether EU trade policy is truly working to condition globalisation according to European values and preferences.
Keywords: 330